Clinical applications of STING agonists in cancer immunotherapy: current progress and future prospects - Wang, Bin; Yu, Wanpeng; Jiang, Hongfei; Meng, Xiangwei; Tang, Dongmei; Liu, Dan (Frontiers in Immunology, 2024)
The STING (Stimulator of Interferon Genes) pathway is pivotal in activating innate immunity, making it a promising target for cancer immunotherapy. STING agonists have shown potential in enhancing immune responses, particularly in tumors resistant to traditional therapies. This scholarly review examines the diverse categories of STING agonists, encompassing CDN analogues, non-CDN chemotypes, CDN-infused exosomes, engineered bacterial vectors, and hybrid structures of small molecules-nucleic acids. We highlight their mechanisms, clinical trial progress, and therapeutic outcomes. While these agents offer significant promise, challenges such as toxicity, tumor heterogeneity, and delivery methods remain obstacles to their broader clinical use. Ongoing research and innovation are essential to overcoming these hurdles. STING agonists could play a transformative role in cancer treatment, particularly for patients with hard-to-treat malignancies, by harnessing the body's immune system to target and eliminate cancer cells.